2010
DOI: 10.1073/pnas.0911494107
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association identifies OBFC1 as a locus involved in human leukocyte telomere biology

Abstract: Telomeres are engaged in a host of cellular functions, and their length is regulated by multiple genes. Telomere shortening, in the course of somatic cell replication, ultimately leads to replicative senescence. In humans, rare mutations in genes that regulate telomere length have been identified in monogenic diseases such as dyskeratosis congenita and idiopathic pulmonary fibrosis, which are associated with shortened leukocyte telomere length (LTL) and increased risk for aplastic anemia. Shortened LTL is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
236
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 249 publications
(247 citation statements)
references
References 55 publications
8
236
3
Order By: Relevance
“…11 Genetic association studies have revealed associations between single-nucleotide polymorphisms (SNPs) in the TERC and TERT genes and TL. [11][12][13][14][15][16][17] Other studies reported associations between SNPs in TERC and POT1 with human longevity, 11,17,18 suggesting that genes regulating TL may influence human longevity.…”
Section: Introductionmentioning
confidence: 99%
“…11 Genetic association studies have revealed associations between single-nucleotide polymorphisms (SNPs) in the TERC and TERT genes and TL. [11][12][13][14][15][16][17] Other studies reported associations between SNPs in TERC and POT1 with human longevity, 11,17,18 suggesting that genes regulating TL may influence human longevity.…”
Section: Introductionmentioning
confidence: 99%
“…This SNP is in strong linkage disequilibrium (LD) with rs12696304 (r 2 ¼0.91). 9 However, it is unclear whether this locus recently identified in Europeans and Americans exerts a similar effect on LTL in the Chinese population. In the present study, we sought to validate these reported associations between SNPs near TERC (rs12696304 and rs16847897) and LTL in 4016 unrelated individuals based on the Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of Ctc1 or Stn1 lengthens G-overhangs [2][3][4]. Genetic variants of Stn1 are associated with increased telomere length in leukocytes [7] and expressing a deletion mutant of Stn1 in cancer cells causes telomere lengthening [5], suggesting that Stn1 may be involved in telomere length regulation. Recently, mutations in Ctc1 have been isolated from patients with telomere disorder dyskeratosis congenita (DC) and patients with Coats Plus (CP) syndrome, a complex genetic disease clinically related to DC [8][9][10].…”
Section: Introductionmentioning
confidence: 99%